Evaluation of the Food Services of a Public University in Rio de Janeiro during the COVID-19 Pandemic - Gomes de Azevedo Medeiros, Maria das Graças; Gomes de Castro, Laura Liz; da Silva Bezerra, Carolina; Pessanha da Penha, Manoela; Soares Lourenço, Maristela (O Mundo da Saúde, 2022)
With the emergence of COVID-19, Food Services (FS) needed to adapt to the protocols established by health agencies to avoid the transmission of the SARS-CoV-2 virus. Although there is no evidence of transmission of the virus through food, contagion can occur between food handlers and customers. In this study, the objective was to evaluate the measures implemented in a university FS in order to prevent the transmission and contagion of COVID-19. The methodology used was descriptive and quantitative. Data collection took place from July to October 2021, through the application of a checklist based on health standards for the prevention of transmission of COVID-19. The results showed that the FS demonstrated non-conformities in some items (28.9%), even though the changes made were in accordance with the guidelines of health agencies. The changes mainly refer to the recommendations of health protocols for the prevention of COVID-19 such as natural ventilation, reinforced cleaning, use of Personal Protective Equipment (PPE) - mask, informative posters, and physical distancing. It is concluded that it is necessary to put into practice the current regulations and correct the possible flaws so that the FS reach all the requirements required by the legislation in the prevention of the transmission of COVID-19.